Pregnancy Ambivalence and Long-Acting Reversible Contraceptive (LARC) Use Among Young Adult Women: A Qualitative Study - Higgins, Jenny A. (Perspect Sex Reprod Health, 2017)
CONTEXT: Many young adults are unclear about how much they want to have, or prevent having, a baby. However, pregnancy ambivalence is an underexamined factor in the uptake of long-acting reversible contraceptive (LARC) methods—IUDs and implants—the most effective methods available. METHODS: In 2014, investigators conducted six focus groups and 12 interviews with 50 women aged 18–29 in Dane County, Wisconsin; participants were either university students or community residents receiving public assistance. A modified grounded theory approach was used to analyze the data. RESULTS: Four themes emerged. First, participants described a pregnancy desire spectrum: Those strongly motivated to avoid pregnancy were most receptive to LARC methods, while those with less clear or mixed desires worried that these methods would prevent “accidental” pregnancies that might not be unwelcome. Second, women within a few years of wanting children perceived LARC methods as too “permanent,” despite awareness of their reversibility. Third, age and life stage were important factors: Younger women and those attending school or beginning careers were more likely than others to consider these methods because they had clearer motivations to avoid pregnancy. Finally, relationship stage influenced receptiveness to LARC methods: Women in newer relationships were more receptive than were those in longer term relationships who imagined having a baby with their partner someday. CONCLUSION: Effectiveness is not the only factor in women’s selection and use of contraceptive methods. Individual preferences will lead some women to choose non-LARC methods even when fully informed of their options.